Improve the Promotion Strategy of PT Intan Makmur Jaya - Andi Kristian; Anthony Sanjaya; Faiqotul Ummah; Lussyana Maria (Journal of the Community Development in Asia (JCDA), 2018)
The world of badminton has always been one of the most popular sports in the world, especially in Indonesia. Indonesia itself is the most respected country, it can be said that Indonesia is home to world badminton and produces many talented athletes. Badminton sports are a lot of sports and frequent tournaments. One of the supporting factors for badminton development is the existing facilities. Like the field, racket, Shuttlecock, etc. Shuttlecock is a very important part of the game of badminton. Therefore, the shuttlecock must be made with good quality so that it can be used comfortably. This is what PT Intan Makmur Jaya tried to do on the LONDON brand shettlecock which had been marketed in the region. This research aims to develop London shuttlecock products especially for exports. This research is development and marketing research. To carry out export quality and marketing methods, this shuttlecock needs to be developed to be able to compete with other shuttlecock products, especially for exports. Competition for shuttlecock products in Indonesia is quite hard, because there are many shuttlecock products on the market. Therefore, it is necessary to develop the quality of shuttlecock production in order to compete with other shuttlecock products at the international level which have their own quality standards. The right marketing step can bring shuttlecock products to export. Keywords: Development of Shuttlecock London, Exports, product quality